Climate action response plans in firms: Understanding the characteristics of firms planning for a more sustainable future - Helena Lenihan; Mauricio Perez-Alaniz; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Firm-level Climate Action Response Plans (CARPs) are strategic plans comprising firms' climate change mitigation and adaptation commitments. Given the importance of CARPs for meeting climate change targets, encouraging firms to develop CARPs is paramount. When designing evidence-based approaches to drive firm-level CARPs, it is essential to know the resources and capabilities that enable firms to develop CARPs. Drawing on novel and highly detailed data on firms in Ireland, and using a direct matching approach, our study examines the characteristics that distinguish firms that develop and do not develop CARPs. We find that firms developing CARPs: (1) Exhibit strong market performance, in terms of productivity and sales; (2) Engage in international markets; (3) Are highly R&D and innovation active; and (4) Already use digital technologies. Such insights suggest that CARPs require firms to have high levels of resources and skills when designing their responses to climate change. The paper proffers potential policy and managerial implications, in terms of encouraging firms to develop CARPs.
Keywords: Q54; Q56; Q57; L21; M14; 330; Firm-level climate action; Climate Action Response Plans; Climate Change Adaptation; Climate Change Mitigation; Firms' R&D and innovation; Greenwashing